Early Ediacaran Magmatism in the Yenisei Ridge and Evolution of the Southwestern Margin of the Siberian Craton - Vernikovskaya, A.; Vernikovsky, V.A.; Matushkin, N.; Kadilnikov, P.; Metelkin, D.V.; Romanova, I.; Li, Zheng-Xiang; Bogdanov, E. (MDPI, 2020)
We present the first comprehensive data for the early Ediacaran stage of evolution of the western active continental margin of the Siberian Craton (Yenisei Ridge). U-Pb (SHRIMP-II SIMS) data for zircons from dikes of picrodolerites, quartz diorites, and leucocratic granites show that they were emplaced at 625 ± 5, 623 ± 8, and 626 ± 5 Ma, respectively, which indicates a narrow time window of Ediacaran magmatic events. The mafic tholeiitic rocks have OIB and E-MORB mantle components in their magmatic sources. Mineralogical and geochemical observations showed that the mantle-sourced mafic melts assimilated some crustal material, forming Th-enriched dikes of intermediate composition and K-and Rb-enriched felsic rocks. The possible geodynamic conditions for the formation of these early Ediacaran dikes are shown and a geodynamic model is presented for the development of the Yenisei Ridge orogen from the late Cryogenian to the late Ediacaran.